A 250 °C Low-Power, Low-Temperature-Drift Offset Chopper-Stabilized Operational Amplifier with an SC Notch Filter for High-Temperature Applications - Zhong Yang; Jiaqi Li; Jiangduo Fu; Jiayin Song; Qingsong Cai; Shushan Qiao (Applied Sciences)
This paper proposes a three-stage op amp based on the SOI (silicon-on-insulator) process, which achieves a low offset voltage and temperature coefficient across a wide temperature range from −40 °C to 250 °C. It can be used in aerospace, oil and gas exploration, automotive electronics, nuclear industry, and in other fields where the ability of electronic devices to withstand high-temperature environments is strongly required. By utilizing a SC (Switched Capacitor) notch filter, the op amp achieves low input offset in a power-efficient manner. The circuit features a multi-path nested Miller compensation structure, consisting of a low-speed channel and a high-speed channel, which switch according to the input signal frequency. The input-stage operational amplifier is a fully differential, rail-to-rail design, utilizing tail current control to reduce the impact of common-mode voltage on the transconductance of the input stage. The two-stage operational amplifier uses both cascode and Miller compensation, minimizing the influence of the feedforward signal path and improving the amplifier’s response speed. The prototype op amp is fabricated in a 0.15 µm SOI process and draws 0.3 mA from a 5 V supply. The circuit occupies a chip area of 0.76 mm2. The measured open-loop gain exceeds 140 dB, with a 3 dB bandwidth greater than 100 kHz. The amplifier demonstrates stable performance across a wide temperature range from −40 °C to 250 °C, and exhibits an excellent input offset of approximately 20 µV at room temperature and an offset voltage temperature coefficient of 0.7 μV/°C in the full temperature range.